HUMAN RESPONSIBILITY FOR GOD’S CREATION IN JEWISH TEACHING AND PRACTICE - Wahle, Hedwig (Journal of Dharma, 2001)
Jewish teaching is based first and foremost on the Bible and its interpretations. The oldest sources of interpretation are the Talmud and the Midrash. These sources in their turn have been interpreted and reinterpreted and continue to be interpreted. In order, therefore, to give an idea of Jewish teaching on ecology today it is necessary to cite both ancient and modern sources.